Recruiting participants to an Internet‐based eating disorder prevention trial: Impact of the recruitment strategy on symptom severity and program utilization. Issue 5 (29th February 2020) - Vollert, Bianka; von Bloh, Paula; Eiterich, Nadine; Beintner, Ina; Hütter, Kristian; Taylor, Craig Barr; Jacobi, Corinna
Abstract: Objective: Using data from a randomized controlled trial, we examined two different strategies to recruit participants for an indicated preventive intervention (StudentBodies‐AN) for women at risk for anorexia nervosa and compared symptom severity and program utilization in participants recruited through each strategy. Method: We recruited participants by announcing the study (a) in lectures at universities and handing out screening questionnaires (face‐to‐face recruitment) and (b) through different media channels, and the participants completed the screening questionnaire on our study website (media‐based recruitment). We compared symptom severity and program utilization between the two groups. Results: A total of 4, 646 women (face‐to‐face: 3, 741, media‐based: 905) were screened and 168 women (face‐to‐face: 114, media‐based: 54) were randomized to the intervention. We found a statistically and clinically significant association between recruitment strategy and symptom severity: Participants who were recruited through media were more likely to fulfill the inclusion criteria (40.6% vs. 13.3%; p < .001) and endorsed significantly more frequently core behaviors and attitudes of disordered eating (EDE global score: 2.72 vs. 2.17, p < .05; Weight Concerns Scale [WCS] score: 66.05 vs. 56.40, p < .05) at baseline than participants recruited face‐to‐face. Also, participants recruited through media were more likely to log onto the program (χ 2 = 5.06; p = .029) and accessed more of the intervention. Discussion: Recruitment through media seems both more feasible and suitable to reach individuals in need of indicative prevention, and should be part of a multimodal recruitment package. Future studies should be explicitly designed to investigate the impact of recruitment modality on reach and effectiveness including cost‐effectiveness analyses.